First record of orca predation on franciscana dolphins (Pontoporia blainvillei) in Argentina - Padula, Antonella Daira; Gana, Joaquín Carlos Mario; Giardino, Gisela Vanina; de León, Marta Carolina; Elissamburu, Andrea; Rodriguez, Diego Horacio; Denuncio, Pablo Ezequiel (Latin American Journal of Aquatic Mammals)
The orca, or killer whale (Orcinus orca), is a cosmopolitan cetacean species that is known as a predator of a wide range of prey, including bony fishes, sharks, sea birds, sea turtles, sea otters, pinnipeds, dolphins, and whales (Jefferson et al., 1991; Visser, 2005; Ford, 2017; Wright et al., 2021). Previous reports of the orca diet off Argentina include broadnose sevengill sharks (Notorynchus cepedianus) (Reyes and Garcia-Borboroglu, 2004), birds (Copello et al., 2021) and marine mammals such as dusky (Lagenorhynchus obscurus) and common (Delphinus delphis) dolphins (Coscarella et al., 2015), southern right whales (Eubalaena australis) (Sironi et al., 2008), South American sea lions (Otaria flavescens) (López and López, 1985; Grandi et al., 2012), and southern elephant seals (Mirounga leonina) (Hoelzel, 1991). However, all these records came from observational studies in Patagonia. In northern Argentina, the trophic ecology of orcas is poorly known. This may be related to the fact that historically orcas seemed to be sporadic visitors near the coast with only a few sightings per year, and that stranding events are very infrequent in this region. However, recent records of sightings suggest that there is an increasing trend in their occurrence in the area (Biología, Ecología y Conservación de Mamíferos Marinos, unpub. data). In the last few years, there were two orca mass strandings in northern Argentina, along the Buenos Aires coast. The first event occurred on 25 August 2018, where six females live stranded between Mar de Ajó (36°43′13″ S, 56°41′16″ W) and Mar del Plata (38°00’ S, 57°33’ W) (Fig. 1); three of them died, and the other three were released. Unfortunately, it was not possible to take samples of these individuals. Fil: Padula, Antonella Daira. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata. Instituto de Investigaciones Marinas y Costeras. Universidad Nacional de Mar del Plata. Facultad de Ciencias Exactas y Naturales. Instituto ...